Regionalism in Africa : genealogies, institutions and trans-state networks - (:unkn) unknown (My University, 2015)
Africa, which was not long ago discarded as a hopeless and irrelevant region, has become a new 'frontier' for global trade, investment and the conduct of international relations. This book surveys the socio-economic, intellectual and security related dimensions of African regionalisms since the turn of the 20th century. It argues that the continent deserves to be considered as a crucible for conceptualizing and contextualizing the ongoing influence of colonial policies, the emergence of specific integration and security cultures, the spread of cross-border regionalisation processes at the expense of region-building, the interplay between territory, space and trans-state networks, and the intrinsic ambivalence of global frontier narratives. This is emphasized through the identification of distinctive 'threads' of regionalism which, by focusing on genealogies, trajectories and ideals, transcend the binary divide between old and new regionalisms. In doing so, the book opens new perspectives not only on Africa in international relations, but also Africa’s own international relations. This text will be of key interest to students and scholars of African politics, African history, regionalism, comparative regionalism, and more broadly to international political economy, international relations and global and regional governance.
Keywords: African Research